HUBUNGAN TINGKAT PENDIDIKAN DAN POLA ASUH ORANG TUA DENGAN PERKEMBANGAN PSIKOSOSIAL ANAK PRA SEKOLAH DI TK AL-ABIDIN BANYUANYAR SURAKARTA - Ratna Indriati; Uun Puput Puspitasari (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
AbstractThe task of psychosocial development of the preschool age is to foster a sense ofinitiative.To support the normal development required appropriate parenting andsupported by parental education. The purpose of this study was to determine thecorrelation between education and parenting with psychosocial development.The subjects were mother of the Kindergarten Al-Abidin Banyuanyar Surakarta.Thisresearch method of design correlation with cross sectional approach method. Thesampling techniques are simple random sampling. The data obtained are then analyzedby chi square test with p = 0.05.The results of research showed Mothers with higher education level as many as 25people (56.82%) and intermediate 19 people (43.18%), parenting democratic as many as38 people (86.4%) and non-democratic 6 people (13.6%), children with appropriatepsychosocial development as many as 37 child (84.1%) and is not suitable 7 child(15.9%). The correlation between education and psychosocial development obtained p =0.395 (p > 0.05), which means that Ho is accepted, the correlation between of parentingand psychosocial development obtained p < 0.001 (p < 0.05), which means Ha isaccepted. It can be concluted that there is no relationship of the educational level with thepsychosocial development and there is relationship of the parenting with the psychosocialdevelopment.Keywords : Level of education, Parenting, Psychosocial Development